1999
DOI: 10.1096/fasebj.13.1.31
|View full text |Cite
|
Sign up to set email alerts
|

A Sos‐derived peptidimer blocks the Ras signaling pathway by binding both Grb2 SH3 domains and displays antiproliferative activity

Abstract: With the aim of interrupting the growth factor-stimulated Ras signaling pathway at the level of the Grb2-Sos interaction, a peptidimer, made of two identical proline-rich sequences from Sos linked by a lysine spacer, was designed using structural data from Grb2 and a proline-rich peptide complexed with its SH3 domains. The peptidimer affinity for Grb2 is 40 nM whereas that of the monomer is 16 microM, supporting the dual recognition of both Grb2 SH3 domains by the dimer. At 50 nM, the peptidimer blocks selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 60 publications
3
90
0
Order By: Relevance
“…While small compounds with impressive SH3 domain blocking activity are still missing, several laboratories, including our own, have successfully introduced SH3 domain binding sequences into living cells to modulate signal transduction events. In the case of Grb2, a recent report showed that a peptide which can interact with both SH3 domains of Grb2 has superior biological activity compared to a peptide targeting just one of the domains (Cussac et al 1999). This study used a binding motif for the Grb2 SH3(C) domain which is derived from the Grb2 SH3(N) domain binding sequence of the SoS protein and has a signi®cantly lower anity for Grb2 SH3(C) than the new binding peptides described here (see Table 3 for anities).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While small compounds with impressive SH3 domain blocking activity are still missing, several laboratories, including our own, have successfully introduced SH3 domain binding sequences into living cells to modulate signal transduction events. In the case of Grb2, a recent report showed that a peptide which can interact with both SH3 domains of Grb2 has superior biological activity compared to a peptide targeting just one of the domains (Cussac et al 1999). This study used a binding motif for the Grb2 SH3(C) domain which is derived from the Grb2 SH3(N) domain binding sequence of the SoS protein and has a signi®cantly lower anity for Grb2 SH3(C) than the new binding peptides described here (see Table 3 for anities).…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies it was found that a murine SoSderived peptide which binds strongly to the Grb2 SH3(N) domain can also bind to the Grb2 SH3(C) domain Cussac et al, 1999). This peptide is known to form a typical type II polyproline helix and contains the P-x-x-P-x-R motif typically found in good Grb2 SH3(N) binding motifs (indicated by ®lled arrow heads below the peptide).…”
Section: Determination Of Grb2 Sh3(c) Binding Peptide Affinities and mentioning
confidence: 99%
“…Isolated N-terminal and Cterminal SH3 domains of Grb2 were obtained by solid phase peptide synthesis as described (50,51). The Sos-derived peptide dimer (VPP-PVPPRRR-Aha-K-Aha-RRRPPVPPPV) was synthesized as described (52). The SH2 domain binding phosphotyrosine m-arylphospho-Tyr-␣-methylphospho-Tyr-Asn-NH 2 tripeptide (pYpYN) was prepared as described (53).…”
Section: Methodsmentioning
confidence: 99%
“…3A), which binds both SH3 domains (Fig. 3B) and blocks the Ras signaling pathway (52). The pYpYN phosphorylated tripeptide, which mimics the targets of the SH2 domain of Grb2, caused a weak inhibition in the absence as well as in the presence of Grb2.…”
Section: Interaction Of the C-terminal Sh3 Domain Of Grb2 With Nwasp mentioning
confidence: 99%
“…These peptides bind with higher a nities than the corresponding peptides completely made up of naturally occurring amino acids. In vivo studies with these compounds are still missing, but it is already clear from the current literature that Grb2 and Crk/CRKL SH3 domain blocker peptides can be carried into cells with peptidevector systems, thereby inhibiting adaptor protein signalling (Cussac et al, 1999;Kardinal et al, 2000Kardinal et al, , 2001Sakkab et al, 2001).…”
Section: Sh3mentioning
confidence: 99%